Neutrality of State Civil Apparatus (Asn) and Its Implications for Their Regional Career Management - Rusliandy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The practice of violations by the State Civil Apparatus (ASN) in the form of non-neutrality in Regional Head Elections, including at the Provincial and Regency/City levels has implications for many irregularities in regional career management. The method taken for this research was a descriptive qualitative approach. The findings of this study revealed that the form of violation of neutrality was participating in or supporting one of the candidate pairs for the regional head. This condition was motivated by their desire to accelerate their career development or maintain a strategic position. Non-neutral practices ultimately have implications for career management that is not based on a merit system and various irregularities, including closed career patterns, prioritized career development for those who are more loyal or meritorious during the Regional Head Election, and mutations that are not following the rules. Best Practice in implementing the merit system in the regions shows that the commitment of the Regional Head is very decisive, as has been done by West Java Province. The elected regional head must be able to control various pressures from the success team or the closest ASN to be consistent with the merit system that has been built. In overcoming the problems that occur, several actions should be taken are: (1) To immediately establish a standard of job competence for JPT and administrative positions. (2) Increase the supervision of the Menpan (Ministry of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia) and RB (Bureaucratic reform), KASN (State Civil Service Commission), BKN (State Civil Service Agency) and Ministry of Home Affairs (3) encourage the function of the personnel auditor optimally to carry out periodic audits related to regional ASN management. (4) Increasing the role of ASN professional organizations so that they can encourage and implement career management based on a merit system.